Navigating Domestic Conflict: The Implementation of Maqasid al-Syari'ah in Sidorejo Village - Ahsan, Ahsan; Zaenab, Zaenab; Hediturmudi, Asep; Hadrawi, Hadrawi; Salam, Abdul (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
This study aims to reveal efforts to resolve disputes within families through a case study in Sidorejo Village, Wonomulyo Subdistrict, from the perspective of Maqasid al-Syariah (primary maslahat). This is a qualitative study. The research design is field research. The primary data sources for this study consist of the Head of Sidorejo Village as a community leader, Yulianti as a resident of Sidorejo Village, Wati as Yulianti's mother and a resident of Sidorejo Village, the Religious Advisor of the Wonomulyo Subdistrict KUA, and the Imam of Sidorejo Village. The results of this study indicate that: First, the causes of family disputes based on the case study in Sidorejo Village, Wonomulyo Subdistrict, are economic problems, differences in opinions and thoughts, and communication and understanding. Second, efforts to resolve family disputes based on the case study in Sidorejo Village, Wonomulyo Subdistrict, through deliberation and mediation show indicators that are in line with hifz al-Din, hifz al-Nafs, hifz al-'Aql, hifz al-Mal, and Hifz al-Nasl.